Evaluation of Albumin-Bilirubin (ALBI) grade in liver cirrhosis (Journal of Shaheed Suhrawardy Medical College, 2025)
Cirrhosis is a condition of liver characterized by the replacement of normal liver tissue by scar tissue due to long term damage by chronic diseases. Early identification and evaluation of the severity of this disease may facilitate timely and proper clinical treatment, thereby reducing mortality. Recently a new grade is introduced, Albumin-Bilirubin(ALBI)grade which is simple, two parameters only, more evidence based and more objective. The purpose of this study was to introduce the ALBI grade in the evaluation of cirrhotic patient.This cross sectional study was conducted at the Department of Laboratory Medicine in collaboration with the Department of Hepatology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from March 2018 to February 2019. Blood samples were assayed from eighty one diagnosed cirrhotic patients. SPSS version 22 was used for all statistical analysis. Regarding prevalence of cirrhosis, 49.4% had HBV. While distribution ofALBI grade - grade1, grade2 and grade3patients were 28.4%, 34.6% and 37% respectively. This study concluded that the newly developed ALBI grade is better  understanding and may be used in cirrhotic patient.J Shaheed Suhrawardy Med Coll 2023; 15(2): 3-5